A TDOA Measurement Technique for Asynchronous Indoor Localization System using UWB-IR - Vashistha, Ankush (2017)
Systems for indoor navigation differ substantially in implementation and maintenance effort as well as in costs. A system must work on any smart phone to ensure broad adoption and avoid isolated solutions. It must also work as automated as possible. A routing graph is commonly used for path planning. But generally, no routing graph exists and it must be computed. We propose a method to compute a routing graph from floor plans. We use conditional erosion to extract the graph. An approximation to the common routes through corridors and rooms can be calculated by a conditional query of every pixel of the grid based floor plan by means of predefined 3 × 3 image matrices. The grid data is then converted to edges and nodes. We evaluate the method on existing floor plan data of a test building of the HafenCity University of Hamburg.